Deletion of HIF-2α in Dendritic Cells Attenuates Anti-Glomerular Basement Membrane Nephritis - Jiayi Miao; Junwen Qu; Dawei Li; Ming Zhang (Biomedicines)
Background: Anti-glomerular basement membrane (anti-GBM) nephritis is mediated by autoantibodies and may progress to end-stage renal disease. Although its pathogenesis is not completely understood, dendritic cells (DCs) have been reported to play an important role in this process. Hypoxia-inducible factor-2α (HIF-2α) has been reported to have a regulatory effect on DCs under hypoxic conditions, while no research has investigated its role in autoimmune nephritis. Methods: Anti-GBM nephritis was induced in CD11c-specific HIF-2α-deficient and WT mice using nephrotoxic serum (NTS). All mice were divided into four groups: (i) WT+PBS, (ii) CD11c-Cre+ Hif2αfl/fl+PBS, (iii) WT+NTS and (iv) CD11c-Cre+ Hif2αfl/fl+NTS. Seven days after induction, renal function, immune cell infiltration and the expression levels of genes in the renal cortex were assessed in each group. Results: On day 7, the levels of serum creatinine and blood urea nitrogen and the urine albumin-to-creatinine ratio were lower for mice with DC-specific deletion of HIF-2α compared with their WT counterparts (p < 0.05). Histopathological analysis showed that there was less crescent formation in the renal cortex with conditional HIF-2α knockout, and the infiltration of DCs and macrophages was also suppressed (p < 0.05). Genes related to antigen processing and presentation were found to be expressed differentially between the two groups, and the activation of the MAPK pathway was affected (p < 0.05). Western blot analysis validated that HIF-2α knockout inhibited the phosphorylation of p38 MAPK (p < 0.05). Conclusions: In this study, we observed a pro-inflammatory effect of HIF-2α in DCs in early anti-GBM nephritis, and the results suggested a regulating effect of HIF-2α on p38 MAPK pathways.